Bragg gratings and Fabry-Perot cavities in low-loss multimode CYTOP polymer fibre - Theodosiou, Antreas; Hu, Xuehao; Caucheteur, Christophe; Kalli, Kyriacos (My University, 2018)
We report the inscription of fiber Bragg gratings (FBGs) and Fabry-Perot (FP) cavities in a gradient index cyclized transparent optical polymer (CYTOP) polymer optical fiber (POF) using a femtosecond laser. Through careful control of the inscription parameters, the coupling between the grating and the fiber’s higher order propagation modes is reduced, allowing for single peak grating spectra. Furthermore, we inscribe a 10-nm chirped grating and an FBG FP cavity with a free spectral range of 240 pm. We measure the group delay of the chirped grating and characterize the fiber FP cavity for strain and temperature.
Keywords: Cavity resonators; Fabry-Perot; Fiber gratings; Fibre Bragg gratings; Gratings; Indexes; Optical fibers; Optical sensors; Polymer fibres; Sensing